Influence of Lactobacillus buchneri on soybean curd residue co-conversion by black soldier fly larvae (Hermetia illucens) for food and feedstock production. (1st March 2019) - Somroo, Abdul Aziz; ur Rehman, Kashif; Zheng, Longyu; Cai, Minmin; Xiao, Xiaopeng; Hu, Shencai; Mathys, Alexander; Gold, Moritz; Yu, Ziniu; Zhang, Jibin
Highlights: Lactobacillus buchneri (L3-9) could enhance SCR conversion and SCR reduction. Lactobacillus buchneri (L3-9) could increase BSFL protein and fat content. Lactobacillus buchneri (L3-9) could enhance the nutritional value of BSFL. Heavy metals and anti-nutritional factor values in BSFL found within the safety intake levels of WHO standard. Abstract: Black soldier fly larvae (BSFL), Hermetia illucens (Diptera: Stratiomyidae) can reduce environmental pollution and convert organic wastes into biomass that is rich in protein and fat. The influence of the nutritional characteristics of organic waste on BSFL characteristics relevant for food and feed safety remains poorly understood. To evaluate the conversion of soybean curd residues (SCR) into high-quality animal-derived proteins and fats for human and livestock consumption, this study assessed the co-conversion efficacy, nutrient composition, safety, and anti-nutritional factor concentrations in BSFL after the development on SCR with Lactobacillus buchneri (L3-9) . SCR was pretreated with L. buchneri (10 8 cfu/ml), and then BSFL was employed for conversion. BSFL fed with SCR and L. buchneri had a significantly higher dry mass reduction (55.7 ± 0.9%), bioconversion rate (6.9 ± 0.3%), crude protein content (55.3 ± 0.6%), and fat content (30.0 ± 0.6%) than SCR (49.0 ± 0.7%, 5.0 ± 0.3%, 52.8 ± 0.3%, and 26.1 ± 0.8%, respectively) and artificial feed (43.9 ± 0.8%, 3.9 ± 0.1%, 50.3 ± 0.4%, and 24.3 ± 0.4%, respectively). However, the feed conversion ratio (8.0 ± 0.3), of BSFL fed with SCR and L. buchneri was lower than that of the BSFL fed with SCR (9.8 ± 0.1) and artificial feed (11.1 ± 0.5). In addition, BSFL had satisfactory concentrations of all essential amino acids and fatty acids required for human consumption as recommended by WHO/FAO/UNU. The heavy metals and anti-nutritional factor concentrations were within the safety intake levels for food and feedstock. Therefore, the addition of L. buchneri with BSFL on SCR did not only increase co-conversion performance but also enhanced the nutritional value of BSFL.